PENGARUH SERTIFIKASI PRODUK HALAL TERHADAP PRAKTEK AKUNTANSI SYARIAH DI INDUSTRI MAKANAN - Cania, Ema Saswita; Nurlaila, Nurlaila (International Journal Mathla’ul Anwar of Halal Issues, 2024)
This study aims to investigate the influence of halal product certification on the application of Sharia accounting practices within the food industry. As the demand for halal-certified products increases globally, it is crucial to understand how such certification affects the accounting practices of companies that adhere to Islamic financial principles. The research employs a quantitative approach, utilizing surveys and interviews with professionals in the food industry to gather data. The findings are expected to reveal the extent to which halal certification impacts the transparency, accountability, and ethical financial reporting of these companies. This study contributes to the literature on Islamic finance and provides practical insights for companies seeking to align their accounting practices with Sharia principles.